Some Dentists in Nantes, France, Who Were Resistance Fighters - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
One day, while I was strolling along the streets of Nantes with my wife and daughter, I became intrigued by a memorial stone located on a staircase of 9, rue Boileau. A few days later, I came back with a pen to write down the text engraved on it. "Here was Pierre Audigé's dental offi ce, a member of the Resistance movement, leader of the "Mouvement Libération-Nord" (a movement created to defend the North of France against the Nazi occupation) of Nantes and the "Basse Loire" region, then leader of the CohorsAsturies network. Appointed in 1942 by Jean Cavaillès, founder of these organizations, he was arrested, tortured by the Gestapo and died in the Nazi slammers in June 1944. He died for France."